2013
DOI: 10.15517/lank.v0i0.11529
|View full text |Cite
|
Sign up to set email alerts
|

Orchids without borders: studying the hotspot of costa rica and Panama

Abstract: aBstract. The Mesoamerican region is one of the richest in orchid diversity in the world. About 2670 species, 10% of all orchids known have been recorded there. Within this region, most of the species are concentrated in the southernmost countries. Costa Rica with 1598 species (or 0.030 spp/km 2 ) and Panama with 1397 species (0.018 spp/km 2 ) stand at the top of endemic species list of all Mesoamerica, with 35.37% and 28.52%, respectively. These figures, however, are misleading, as political boundaries do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Our results strongly correspond with earlier studies made upon Orchidaceae of Mesoamerica. According to Ossenbach, Dressler & Pupulin (2007) and Bogarín et al (2013) about 10% (ca. 2700 taxa) of all orchid species known all around the world are recorded from this area, of which almost 29% are endemic to Panama.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results strongly correspond with earlier studies made upon Orchidaceae of Mesoamerica. According to Ossenbach, Dressler & Pupulin (2007) and Bogarín et al (2013) about 10% (ca. 2700 taxa) of all orchid species known all around the world are recorded from this area, of which almost 29% are endemic to Panama.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on regional diversity published by Barthlott, Lauer & Placke (1996) indicated that the region from eastern Costa Rica, through Panama to western Colombia has the highest plant biodiversity on the globe. In Panama, the extraordinary biodiversity is a consequence of an unusual mosaic of habitat types and an intermingling of species from both Central and South America, including single species of Psilochilus , but also many other Orchidaceae taxa (D’Arcy, 1987; Condit et al, 1996; Ossenbach, Dressler & Pupulin, 2007; Bogarín et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Our results strongly corresponds with earlier studies made upon Orchidaceae of Mesoamerica. According to Ossenbach et al (2007) and Bogarín et al (2013) about 10% (ca. 2700 taxa) of all orchid species known all around the world are recorded from this area, of which almost 29% are endemic to Panama.…”
Section: Biogeography and Diversitymentioning
confidence: 92%
“…with representatives in South America are distributed in Panama. The bias resulting from less floristic and alpha-taxonomic work in Panama should be reduced in the upcoming years(Bogarín et al 2013). Our focus is on studying the factors that led to the formation of the current species composition of Orchidaceae in the Isthmus.…”
mentioning
confidence: 99%